Child, Family, and Community - Laff, Rebecca; Ruiz, Wendy; Open Textbook Library (Open Textbook Library, 2019)
Over the years researchers have found the necessity to develop theories of behavior that are specific to family settings. These theories have been developed by people with a variety of areas of emphasis, from family therapists to gerontologists to child development specialists. In this chapter we will briefly discuss six such theories: Bioecological Model, Family Systems, Functionalism, Conflict Theory, Symbolic Interactionism, and Psychological Perspectives.
Chapter 1: Theories That Help Us Understand Families -- Chapter 2: How Children Learn and Understand Their World -- Chapter 3: What is Culture and Why is it Important? -- Chapter 4: How Does Gender Influence Children, Families and Communities? -- Chapter 5: What is a Family? -- Chapter 6: A Closer Look at Parenting -- Chapter 7: Building Trusting Collaborative Relationships with Families -- Chapter 8: Welcoming & Supporting Families -- Chapter 9: Creating Positive Goal-Oriented Relationships with Strengths-Based Attitudes and Relationship-Based Practices
In English.
Description based on online resource
Keywords: Sociology -- Textbooks